Effect of Hyaluronan in Collagen Biomaterials on Human Macrophages and Fibroblasts In Vitro - Nancy Avila-Martinez; Maren Pfirrmann; Madalena L. N. P. Gomes; Roman Krymchenko; Elly M. M. Versteeg; Marcel Vlig; Martijn Verdoes; Toin H. van Kuppevelt; Bouke K. H. L. Boekema; Willeke F. Daamen (Journal of Functional Biomaterials)
In adults, scars are formed after deep skin wound injuries like burns. However, the fetal microenvironment allows for scarless skin regeneration. One component that is abundantly present in the fetal extracellular matrix is hyaluronan (HA). To study whether biomaterials with HA improve wound healing, type I collagen scaffolds with and without HA were prepared and characterized. Their immune effect was tested using macrophages and their phenotypes were analyzed through cell surface markers and cytokine expression after 48 h. Since fibroblasts are the main cellular component in the dermis, adult, fetal and eschar-derived cells were cultured on scaffolds for 14 days and evaluated using histology, gene and protein expression analyses. Biochemical assays demonstrated that HA was successfully incorporated and evenly distributed throughout the scaffolds. Macrophages (M0) cultured on Col I+HA scaffolds exhibited a profile resembling the M2c-like phenotype (CD206high, CD163high and IL10high). HA did not significantly affect gene expression in adult and fetal fibroblasts, but significantly reduced scarring-related genes, such as transforming growth factor beta 1 (TGFB1) and type X collagen alpha 1 chain (COL10A1), in myofibroblast-like eschar cells. These findings highlight the potential of incorporating HA into collagen-based skin substitutes to improve the wound healing response.